Body composition of male and female Chilean powerlifters of varying body mass - Patricio Palma-Lafourcade; Diego Cisterna; Jordan Hernandez; Rodrigo Ramirez-Campillo; Cristian Alvarez; Justin W. Keogh
Abstract Aim: To examine body composition of Chilean powerlifters according to body mass and sex. Methods: Fifty-six male and female powerlifters were recruited from one national competition. Aside from the official weight categories, males were classified as the lightweight, middleweight, and heavyweight classes. Similarly, females were classified as lightweight and middle-heavyweight classes. Nineteen anthropometric measures were assessed, with lean mass as the main outcome. A one-way ANOVA was used to compare groups. Results: Male lightweight class lifted less (p<0.01) total load (417±30.9 kg) compared to heavier male classes (524±66.7 kg, middleweight; 581±131 kg, heavyweight), and female classes lifted less (p<0.01) total load (221±33.8 kg, lightweight; 254±48.3 kg, middleweight-heavyweight) compared to all male classes. Regarding lean-mass in trunk, arms and legs, total body protein, water, and mineral mass, all male groups had greater (p<0.01) values than the groups of females, while lightweight males had lower (p<0.01) values than the rest of male groups, and heavyweight males had greater (p<0.01) values than the total sample of males (except for legs lean mass, and total bone mineral content). In females, no significant differences were observed between classes, or in total load lifted or in body composition. Conclusion: Heavier male lifters had significantly greater lean mass than lighter athletes. Therefore, powerlifting performance was affected by anthropometric measures, as corroborated by 1-RM scores. However, there was a general lack of differences in body composition between female weight classes, and, as a result, a lack of differences in 1RM performance.